Comparison between Interrupted X Suture and Continuous Suture for Closure of Midline Incision in Emergency Laparotomy : A Randomized Controlled Trial (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Wound dehiscence is disruption of any or all of the layers in a wound. At around 7–10 days post operatively leakage of clear sero-sanguinous fluid from the wound is usually the first indicator of burst abdomen. The patient usually feels something ‘giving away’ at this time.It may occur in 3-14.5% cases and is very distressing to the patient.Number of methods of closure of midline laparotomy wound have been introduced in the past to prevent this outcome. The study to compare the result of continuous and interrupted closure of midline emergency laparotomy in respect of burst abdomen.Materials and methods: This randomized controlled trial study was carried out in the Department of Surgery Chittagong Medical College Hospital, Chattogram, duration January 2017 to December 2017. A total of 500 patients were enrolled in this study. Data were collected, statistical analyses were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-23).Results: 250 patients in group A and 250 in B. Surgical wound related post-operative complications were found in 30.4% of the study subjects (n=152).Wound dehiscence was found in 11% subjects, surgical site infection was found in 18.4% subjects and incisional hernia in 1%.All these complications were significantly higher in continuous suture group than interrupted group (p